Effects of various modeling assumptions on steady-state and transient performances of single-phase natural circulation loop. (May 2021) - Sahu, Mayaram; Sarkar, Jahar; Chandra, Laltu
Abstract: It is necessary to investigate the relative effect of various phenomena before neglecting the same for simulating the single-phase natural circulation loop to obtain an acceptable prediction. Hence, the present study focuses on the validation and effect of different assumptions related to Boussinesq approximation, property variation, bend effect, heat loss, axial fluid and wall conduction on the transient and steady-state characteristics. Effect of assumptions for different working fluids (water, brines and hybrid nanofluids), and assess the effect of different heat flux distributions, like uniform, linear, non-linear, sinusoidal and Gaussian, applied to heater are also explored. Mass flow rate (predicts heat transport capability), effectiveness (predicts heat transfer ability) and entropy generation rate (predicts irreversibility) are evaluated. The results disclose that the Boussinesq approximation with constant other properties under-predicts the steady-state mass flow rate and effectiveness and over-predicts the entropy generation rate. This assumption cannot be applied for all working fluids. The fluid and solid conduction is the crucial parameter for simulating transient characteristics. Gaussian heat flux distribution shows the highest mass flow rate and non-linear increasing heat flux shows the highest effectiveness and entropy generation rate. This study will help to consider reasonable assumptions for the numerical simulation.